2017
DOI: 10.21860/medflum2017_179758
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ocular surface squamous neoplasia: Case reportof ocular surface squamous neoplasia: Case report

Abstract: Abstract. Aim: Ocular surface squamous neoplasia (OSSN) is a term that encompasses a wide and varied spectrum of very rare dysplastic disease of cornea and conjunctiva, ranging from conjunctival intraepithelial neoplasia (CIN), carcinoma in situ (CIS) to invasive squamous cell carcinoma (SCC) of conjunctiva and/or cornea. Case report: In our case report, we present squamous cell carcinoma of the conjunctiva and cornea in a 78-year old man. Our diagnostic algorithm included: slit lamp and fundus examination, go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Rayner and Van (2006) and Malalana et al, (2010) who observed, equine ocular squamous cell carcinoma was successfully treated with Mitomycin eye drops without any recurrence after LASER ablation. Chen et al, (2004), Gupta and Muecke (2010), Walia et al, (2016), Merlak et al, (2017) and Antonietta Blasi et al, (2018) treated ocular surface squamous neoplasia using Mitomycin without any recurrence in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Rayner and Van (2006) and Malalana et al, (2010) who observed, equine ocular squamous cell carcinoma was successfully treated with Mitomycin eye drops without any recurrence after LASER ablation. Chen et al, (2004), Gupta and Muecke (2010), Walia et al, (2016), Merlak et al, (2017) and Antonietta Blasi et al, (2018) treated ocular surface squamous neoplasia using Mitomycin without any recurrence in humans.…”
Section: Resultsmentioning
confidence: 99%